Sustainable Tertiary Accelerator of Sulfur Vulcanization of NR and SBR Rubbers From Natural Tree Extract (Baghdad Science Journal, 2024)
A novel natural, low cost and available accelerator for Styrene Butadiene Rubber (SBR) and Natural Rubber (NR) curing systems was prepared from waste agriculture. Dried powder of Conocarpus lancifolius leaf extract (CLLE) was added by (0.5, 1.0 ,1.5 and 2.0) wt% for SBR and NR master batches individually containing benzothiazole accelerators (MBT, MBTS). (CLLE) was selected due to the presence of Flavonoids, Saponins and phenols within its structure, which promotes hydrogen bonding (H-bonds) as a secondary bonding, which in turn enhances the curing rate.Results showed that CLLE has an ability to accelerate curing systems and its optimum concentration is 0.5 pphr  for SBR and 1pphr for NR. Its effects on NR curing system is higher than on  SBR system, where with SBR, the optimum curing time (tc90) decreased  only by 2.42%, while with NR, it decreased by 17.74% and the curing rate index (CRI), increased with SBR only by 5.9% , while increased by 24.83% with NR. Also, CLLE addition reduced the scorch time (ts2) of both two rubbers. The ts2 for SBR-based samples are always higher than those for NR-based samples. In addition to that, CLLE caused opposite effects on torques of SBR and NR, and had no effects on tensile strength, slight decreasing in hardness, increasing in modulus at 300% elongation and increasing in stresses and strains before failure. The addition of CLLE increased curing rates due to the active components (Flavonoids, Saponins and phenols), which encouraged using these elastomeric products for bio applications and act as a coupling agent for hydrophilic and hydrophobic polymers.